2017
DOI: 10.1007/s13300-017-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like Peptide-1 Receptor Agonist Treatment Attributes Important to Injection-Naïve Patients with Type 2 Diabetes Mellitus: A Multinational Preference Study

Abstract: IntroductionGlucagon-like peptide-1 receptor agonists (GLP-1RAs) differ in efficacy, side effects, dosing frequency, and device-related attributes. This study assessed the relative importance of treatment-related attributes in influencing preferences for GLP-1RAs among injection-naïve patients with type 2 diabetes mellitus (T2DM).MethodsInjection-naïve T2DM patients from five countries completed a Web-based discrete choice experiment (DCE) survey. Patients chose between hypothetical treatment profiles reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 38 publications
(55 reference statements)
1
54
0
Order By: Relevance
“…It is possible that the higher persistence observed with dulaglutide may be related to dulaglutide’s convenient dosing schedule and ready-to-use single dose pen. Dosing frequency, ease of preparation, and delivery system have been identified as key drivers of patient preference for GLP-1 RAs [ 48 50 ]. Patient preference studies conducted in the UK and Japan have suggested an overall preference for dulaglutide compared to liraglutide [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the higher persistence observed with dulaglutide may be related to dulaglutide’s convenient dosing schedule and ready-to-use single dose pen. Dosing frequency, ease of preparation, and delivery system have been identified as key drivers of patient preference for GLP-1 RAs [ 48 50 ]. Patient preference studies conducted in the UK and Japan have suggested an overall preference for dulaglutide compared to liraglutide [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a multitude of factors can affect treatment adherence, treatment-related issues (e.g. treatment complexity, convenience, cost) are among those considered especially important 11,14 . Adherence improves as dosing frequency decreases, for example, from once daily to once weekly 11,21 .…”
Section: Discussionmentioning
confidence: 99%
“…As many as 55% of patients do not adhere to their prescribed diabetes treatment regimen 6 , compromising the effectiveness of therapy and raising associated costs, healthcare utilization and even mortality risk [7][8][9][10][11][12][13] . Patient adherence to a given medication can be affected by many factors, including dosing regimens, medication costs and general patient preferences 14 . In patients with T2DM, adherence has been shown to increase with the use of prefilled pens compared with vials and syringes for administration of basal insulin 11,[15][16][17][18][19][20] , and through simplified dosing regimens 11,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in subcutaneous injection of large-volume single doses up to 2 mL or more can be attributed to three major causes. First, dosing frequency has been identified as an important factor driving treatment choices across disease states [20][21][22]. In fact, the complexity of the dosing regimen in terms of frequency, flexibility, and timing has a greater importance on patient perceptions than the efficacy and safety profile of drugs [23].…”
Section: Introductionmentioning
confidence: 99%